2022
DOI: 10.1515/jcim-2022-0054
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and blood sugar-lowering effects of purified gambir on diabetic hypertensive Wistar Kyoto rats

Abstract: Objectives Antioxidants protect people from diabetes and its cardiovascular complication. Purified gambir (Uncaria gambir Roxb.) is a potential medicinal plant for treating this condition based on the antioxidant activity of its catechin compound. This study tries to reveal the potential activity of purified gambir as a blood pressure-lowering drug while lowering blood glucose in diabetic hypertensive rats induced by oral NaCl-Prednisone and Alloxan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Furthermore, purified gambier in small doses can improve kidney function and lower blood sugar levels. This can be seen from the value of creatinine clearance, which increased to close to normal values until the end of the experiment after experiencing a decrease due to kidney disorders and related to previous research [13].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, purified gambier in small doses can improve kidney function and lower blood sugar levels. This can be seen from the value of creatinine clearance, which increased to close to normal values until the end of the experiment after experiencing a decrease due to kidney disorders and related to previous research [13].…”
Section: Discussionsupporting
confidence: 80%
“…An Accu-check active glucometer (Roche, Germany) was used to test blood glucose levels in the rat tail. The rats were defined as diabetic after two consecutive measurements of blood glucose above 250 mg/dl and a fasting blood glucose (FBG) level greater than 126 mg/dl [13].…”
Section: Diabetic Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been reported in the literature. [18][19][20][21][22][23] The presence of alkaloids and other bioactive compounds invokes the medicinal characteristics of the plants and their therapeutic use in various pharmacopoeias. 24,25 Sub-acute toxicity, animal observation, body weight, food intake and water consumption measurement A sub-acute oral toxicity study in BALB/c mice indicated zero mortality after repeated VALAF administration for 21 days.…”
Section: Physicochemical and Phytochemical Analysismentioning
confidence: 99%
“…On the fifth day after streptozotocin induction, the blood glucose levels of the test animals were measured using Easy Touch ® GCU. The consistency and evaluation between the blood glucose levels measured by glucometers and plasma glucose levels measured by a laboratory biochemical test in rats have been done in our previous research [17].…”
Section: Diabetes Inductionmentioning
confidence: 99%